Influence of Capital Structure, Liquidity, and Profitability on Firm Value with Dividend Policy as an Intervening Variable in Manufacturing Companies Listed on the Indonesia Stock Exchange - Dwi Afriliandy Lasmo; Dedi Hariyanto (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to address this gap by analyzing the effect of capital structure, liquidity, and profitability on firm value, with dividend policy as a mediating variable, focusing on manufacturing companies listed on the IDX in 2023 and 2024. This quantitative study uses secondary data from the Indonesia Stock Exchange and official company websites. The data consist of financial statements from manufacturing companies listed on the IDX during 2023–2024. Samples were selected through purposive sampling with these criteria: listed during 2023–2024, distributed dividends, and had accessible financial reports. Based on the analysis of manufacturing companies listed on the Indonesia Stock Exchange in 2023–2024, capital structure, liquidity, and profitability each significantly affect dividend policy, where sound capital structure, strong liquidity, and high profitability support greater dividend distribution. Liquidity and profitability also have a direct positive impact on firm value, while capital structure negatively affects it due to financial risk. Dividend policy significantly enhances firm value by signaling stability to investors. Furthermore, dividend policy mediates the relationship between liquidity and firm value, but it does not mediate the effects of capital structure or profitability on firm value.